Photocatalytic degradation of Aqueous C.I Reactive violet 5 using bulk zinc oxide (ZnO) slurry - Cabansag, Jeannie Lynn J.; Dumelod, Jesus C.; Alfaro, John Cyrus O.; Arsenal. John D.; Sambot, Jolivette C.; Enerva, Lorna T.; Leaño, Julius L. Jr. (2013)
The degradation of aqueous C.I. Reactive violet 5 dye under UV light with bulk zinc oxide (ZnO) slurry as the photocatalyst was studied. The effects of varying amounts of zinc oxide, dye concentration, exposure time, pH, temperature and lamp intensity on degradation were evaluated. UV irradation was found to enhance dye degradation by about 90% immediately after 30 minutes of exposure time, for low dye concentration of 2 x 10-5 M. The rate of dye degradation increased as the amount of zinc oxide increased until optimum loading was achieved. At 3840 ppm ZnO concentration, 5 x 10-5 M (40 ppm) dye is degraded by 74% after 30 min of irradiation and was nearly 100% degraded after 90 min at pH 7 and temperature of 30°C. The degradation rate follows a first order kinetics with respect to dye concentration, with the rate constant decreasing as dye concentration increases at constant amount of zinc oxide. The rate of RV5 degradation is determined at 9.3 x 10-5 M/h using 3840 ppm ZnO under neutral pH, temperature of 30°C and 20W lamp intensity. Increased pH, temperature and lamp intensity further accelerate dye degradation by about 38.0%, 53.3%, and 43.2%, respectively. The use of zinc oxide provides a simple and efficient method for photocatalytic degradation of azo dyes in wastewater.
Keywords: Photocatalysts; Zinc oxide